Formulation and In-Vitro Evaluation of Gastro-Retentive Floating Tablet of Furosemide - Pradyumna Chaudhari; Deepak G.R.; Roshan Kumar Mehta (Journal of Universal College of Medical Sciences, 2025)
INTRODUCTION 4-chloro-2-(furan-2-ylmethylamino)-5-sulfamoylbenzoic acid (Furosemide) is high efficacious diuretic, used to treat edema and congestive heart failure. Gastro retentive floating tablets offer advantages by retaining in the stomach for a sufficient time against all physiological barriers. It improves bioavailability, reduces drug wastages, and improve the solubility of drug in high pH environment. The crucial aspect is to increase the dissolution time. MATERIAL AND METHODS An experimental design was done in the pharmaceutic laboratory of department of pharmacy from August 2022 to January 2023. Gastro-retentive floating tablets were prepared by direct compression method using different viscosity grades of polymers with sodium bicarbonate and were lubricated with magnesium stearate and talc. The parameters before and after compression were evaluated. RESULTS All the hydro-dynamically balanced system formulations showed good in-vitro floating properties. The tablet of F4 formulation was best which shows drug release up to 12 hours with percentage cumulative drug release up to 99.04 %. CONCLUSION The preparation shows successful approach to maintain the sustain release of furosemide at different time interval. Among formulations, floating tablet formulated using 100 mg Hydroxypropyl methylcellulose K15 M (HPMC K15M) polymer was found to be best.